Non-alcoholic fatty liver disease increases the risk of cardiovascular disease in young adults and children: a systematic review and meta-analysis of cohort studies - Liao, Yan-Lin; Zhu, Gen-Yuan; Chang, Cheng (Frontiers in Cardiovascular Medicine, 2024)
Background and aims: It is uncertain if there is a link between non-alcoholic fatty liver disease (NAFLD) and cardiovascular diseases (CVD) in young adults and children. To evaluate the potential link between these two conditions, we conducted a systematic review and meta-analysis of cohort studies.Methods: A comprehensive search was conducted in PubMed, Web of Science and Embase in order to locate all relevant cohort studies published until August 2023. Random effects meta-analyses were conducted using the generic inverse variance method, with additional subgroup and sensitivity analyses. The Newcastle-Ottawa Scale was employed to evaluate the methodological quality.Results: Four cohort studies (eleven datasets) involving 10,668,189 participants were included in this meta-analysis.This meta-analysis demonstrated that NAFLD increases the risk of CVD in young adults and children (HR = 1.63, 95% CI: 1.46-1.82, P < 0.00001). Further subgroup analyses showed that individuals with NAFLD were at a heightened risk of coronary heart disease (CHD) (